Primary Intraocular Lymphoma in a Patient with Bilateral Epstein-Barr Virus Panuveitis - Seyedeh Maryam Hosseini; Mojtaba Abrishami; Elham Barashki; Ghodsieh Zamani (Case Reports in Ophthalmological Medicine)
Purpose. Herein, we report a case of primary intraocular lymphoma (PIOL) with the first presentation of bilateral Epstein-Barr virus- (EBV-) associated panuveitis. Case Presentation. A 69-year-old male was referred with a three-day history of blurred vision and pain and redness in his left eye following cataract surgery. Examination revealed panuveitis, vitritis, and necrotizing retinitis with retinal hemorrhage. A month later, the right eye was also involved. Polymerase chain reaction-based analysis of the vitreous sample was positive for EBV, and cytological evaluation was compatible with the diagnosis of B-cell lymphoma. A significant improvement was observed following serial intravitreal rituximab and methotrexate injections. The central nervous system and lungs were involved after 6 months, and the patient expired despite systemic chemotherapy. Conclusion. There may be an association between EBV panuveitis and primary intraocular B-cell lymphoma.